Mulheres XY e a Síndrome de Insensibilidade aos Andrógenos - João Edson Marques Bandeira; Regiane Geralda Rosa de Sales; Isabela Louise Caldeira Silva; Brenda Miranda Aidar; Mariana Bratz da Silva; Ana Lígia Barros Marques (UniEVANGÉLICA, 2015)
Objective: The aims are to report a case of Androgen-Insensitivity Syndrome (AIS) and discuss aspects of opportune diagnosis and treatment of AIS. Case Report: C.F.F., 35, sought medical assistance reporting overweight and hypertension. During the anamnesis did not present menarche; with normal breast development, but late, around 14 years. Physical examination shows normal female external genitalia, with scarce pubic hair (P2) and the absence of axillary hair; breasts with normal development (M5). Conclusions: The result of the G band karyotype was 46, XY for the sisters and the screening in relatives revealed prepubescent girl with XY karyotype. The risk of tumor development is difficult to be predicted recently markers were identified that may be useful in determining individual risk and suggest the time of gonadectomy. The current consensus on the approach related to intersex disorders recommends gonadectomy at diagnosis for patients with AIS, after puberty, due to the ease of hormone replacement.